Talking heads : language, metalanguage, and the semiotics of subjectivity - Lee, Benjamin, 1948- (e-Duke books scholarly collection., 1997)
"Talking Heads synthesizes the views and works of a breathtaking range of the most influential modern theorists of the humanities and social sciences, including Austin, Searle, Derrida, Jakobson, Bakhtin, Wittgenstein, Peirce, Frege, Kripke, Donnellan, Putnam, Saussure, and Whorf. After illuminating these many strands of thought, Lee moves beyond disciplinary biases and re-embeds within the context of the public sphere the questions of subjectivity and language raised by these theorists. In his examination of how subjectivity relates not just to grammatical patterns but also to the specific social institutions in which these patterns develop and are sustained, Lee discusses such topics as the concept of public opinion and the emergence of Western nation-states."--Jacket